The factors affecting the green brand equity of electronic products: Green marketing - Narges Delafrooz; Armin Goli; Len Tiu Wright (Cogent Business & Management, 2015)
This study is intentionally functional, and, from the data collection aspect, is a descriptive survey. The statistical data for the present study includes low-power electronic and electric products in Guilan Province. A total of 384 consumers were chosen using the random cluster sampling method. We have used confirmatory factor analysis and structural equation modeling to analyze the given data. The findings show that there is a significant relationship among brand-perceived quality, green brand image, (GBI) and brand value, but not with the green brand-perceived value (GBPV). In addition, the results of the study show that brand credibility has a significant relationship with the GBPV and GBI, but not with the GBPV and GBI, each of which are associated with the green brand in a different way. At the end of this survey, you will read about the intermediate variables, all of which are acceptable, except the intermediate variables of brand credibility and GBI.
Keywords: 650